112k views
3 votes
Find the limit. Use l'Hospital's Rule if appropriate. If there is a more elementary method, consider using it. lim x→[infinity] (5x − 3/5x + 2)^ 5x + 1

1 Answer

1 vote

Answer:


\lim_(x\rightarrow \infty)((5x-3)/(5x+2))^(5x+1)=e^(-5)

Explanation:

We are given that


\lim_(x\rightarrow \infty)((5x-3)/(5x+2))^(5x+1)

When substitute limit x tends to infinity then it is
1^(\infty) which is indeterminant form

Wheny=
\lim_(x\rightarrow \infty) f(x)^{g(x))

and
1^(\infty)

Then use
y=e^{\lim_(x\rightarrow \infty) g(x)(f(x)-1)}

We have g(x)=5x+1 and f(x)=
(5x-3)/(5x+2)

Substitute the values in the formula


y=e^{\lim_(x\rightarrow \infty)(5x+1)((5x-3)/(5x+2)-1)}


y=e^{\lim_(x\rightarrow \infty)((-5(5x+1))/(5x+2))}


y=e^{\lim_(x\rightarrow \infty)((-5(1+(1)/(5x)))/(1+(2)/(5x)))}


y=e^(-5)


(1)/(\infty)=0

User Swietyy
by
5.8k points